ARTISTIC AND AESTHETIC FEATURES OF THE WORK OF ALEXANDER ARKADEVICH FEINBERG (ILMIY TADQIQOTLAR VA YANGI OLAM, 2026)
Abstract.This scientific article analyzes the artistic and aesthetic features of the work of Alexander Arkadevich Feinberg, a poet and translator who played an important role in the literary environment of Uzbekistan. The poet's poetic heritage, poetic thought, artistic style, and translation activities are studied. His contribution to the development of cultural relations between Uzbek and Russian literature through his work is also highlighted. The results of the study show that Feinberg's work is one of the important factors of intercultural literary dialogue.